Patient decision making in recovering from surgery - Papautsky, Elizabeth Lerner (Frontiers in Psychology, 2023)
Patient work in surgery recovery is fraught with complex judgments and decisions. These decisions are not unlike ones that professionals make that we traditionally study with the Naturalistic Decision Making (NDM) theoretical lens and methods. Similarly, patients are making decisions in naturalistic settings and doing so with the objective of minimizing risk and maximizing safety. What is different is that patients are put in a position to perform complex, high level, high consequence work in the absence of any training, education, or decision support. Using a lived experience, I illustrate that the burden of judgement and decision making in surgery recovery work (e.g., caring for surgical sites, managing drains, managing medications, supporting activities of daily living) can be understood through a macrocognitive paradigm. Thus, the NDM theoretical lens and the associated methods is appropriate to study this problem space.